Editorial: The message, the medium and the market - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The process of market liberalization, the demise of state marketing boards and the lifting of price controls, have created a vacuum for farmers in many developing countries - in terms of information on the pricing of their produce and farm inputs, commodi